Library Purchasing Consortia in the UK - Ball, David; Friend, Frederick (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
The distribution of library purchasing consortia across the United Kingdom is uneven and sector-dependent. Only higher education libraries show a well developed regional infrastructure of purchasing consortia covering virtually all eligible libraries. While there are clear sectoral disparities amongst the library purchasing consortia surveyed, the size of consortium expenditure seems to determine whether procurement professionals are involved. Thus in those whose spend consistently exceeds European Commission guidelines’ thresholds, the involvement of purchasing professionals is much more likely, and also crucial to the successful navigation of such procedures.